Meeting middle managers’ accounting information needs for decision-making - Köykkä, Janne (My University, 2020)
Management reports are used to communicate information forward in corporations. Naturally, the quality of reports has a significant impact on corporations when managers rely on them in decision-making. It has been found that insufficient information quality leads to mediocre decision-making, and that information in management reports may not be aligned with the needs of their recipients. This thesis sheds light on management reporting practices and investigates how management accounting information is being utilised in decision-making. More specifically, the type of information middle managers need and use in decision-making is studied. Furthermore, the qualities of good reporting practices are investigated. The theoretical framework of this thesis consists of three main topics; internal reporting, performance measurement and financial planning and forecasting. The theory part dis-cusses things related to the content of management reports and measures used in managerial decision-making. Additionally, the role of yearly targets and their alternatives are dis-cussed. This thesis is conducted as qualitative research, and the research method used is action research. Data for the empirical part of this thesis was gathered by making observations and conducting interviews at a case company operating in project business. The results show that management reports need to be simplified and provide future-orientated information, and that both financial and non-financial measures should be used. Additionally, it was found that reporting practices of business units that belong to corporate groups have distinguishing qualities. Requirements come from multiple sources which affects the work of business units’ managers and controllers. It was found that managers need forecasts and profit and loss statement of their own responsibility area and that receiving only upper-level information is not adequate. It was also found that flexible formats of re-porting better meet the needs of business unit managers, rather than standard formats imposed by the parent company. The requests from the parent company can be difficult and time-consuming to fulfil, and they might not be relevant for a single location. Therefore, it is suggested that using a top-down approach should be avoided in target setting, and that business units should have more authority to decide on things related to reporting, performance measurement and target setting.
Keywords: management accounting, performance measurement, financial planning